2017
DOI: 10.1038/s41598-017-14790-2
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid signaling maintains epithelial and mesenchymal progenitors in the developing mouse ureter

Abstract: The differentiated cell types of the mature ureter arise from the distal ureteric bud epithelium and its surrounding mesenchyme. Uncommitted epithelial cells first become intermediate cells from which both basal and superficial cells develop. Mesenchymal progenitors give rise to separated layers of adventitial fibrocytes, smooth muscle cells and lamina propria fibrocytes. How progenitor expansion and differentiation are balanced is poorly understood. Here, we addressed the role of retinoic acid (RA) signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
1
12
1
Order By: Relevance
“…These changes correlated with an increase of the RA target gene Rarb at E12.5 (1.6‐fold) and E14.5 (1.2‐fold) (Figure B,C and supplementary material, Table S10). Comparing the list of genes up‐regulated in the Gata2cKO microarray ( n = 219) with the list of genes up‐regulated in ureters treated with RA ( n = 548) that we established recently , we found that a highly significant ( p < 8.91 × 10 −18 ) number of genes ( n = 30) were common to the two lists (Table ), including Cd83 , Ecm1 , Hey2 , and Pou3f1 , whose increased expression in Gata2‐ deficient UM we had already confirmed by in situ hybridisation. This suggests that increased RA signalling contributes to transcriptional changes in Gata2cKO ureters and that reduced degradation of RA at least partly underlies this phenomenon.…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…These changes correlated with an increase of the RA target gene Rarb at E12.5 (1.6‐fold) and E14.5 (1.2‐fold) (Figure B,C and supplementary material, Table S10). Comparing the list of genes up‐regulated in the Gata2cKO microarray ( n = 219) with the list of genes up‐regulated in ureters treated with RA ( n = 548) that we established recently , we found that a highly significant ( p < 8.91 × 10 −18 ) number of genes ( n = 30) were common to the two lists (Table ), including Cd83 , Ecm1 , Hey2 , and Pou3f1 , whose increased expression in Gata2‐ deficient UM we had already confirmed by in situ hybridisation. This suggests that increased RA signalling contributes to transcriptional changes in Gata2cKO ureters and that reduced degradation of RA at least partly underlies this phenomenon.…”
Section: Resultssupporting
confidence: 53%
“…Recently, we profiled by microarray analysis the transcriptional changes caused by manipulation of RA signalling in explant cultures of E12.5 mouse ureters. Amongst the 228 genes that were positively regulated by RA signalling was the transcription factor gene Gata2 . Here, RNA in situ hybridisation revealed a dynamic pattern of Gata2 expression in ureter development (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations